Season of birth influences the timing of first menstruation - Kliś, Katarzyna; Jarzebak, Krzysztof; Borowska-Strugińska, Beata; Mulawa, Agnieszka; Żurawiecka, Martyna; Wronka, Iwona (American journal of human biology, 2016)
Objectives The purpose of this study was to determine whether the month of birth influences the maturation rate of Polish females from two birth cohorts, namely 1982–1984 and 1992–1994. It was also verified whether socioeconomic status (SES) is capable of altering the above relationship. Methods The research material consisted of data collected in two cross‐sectional surveys. The first cohort involved 1,008 female secondary‐school students, the second, 671 female university students. Information on subjects' date of birth, SES, and the age at menarche was obtained from a questionnaire. The subjects were divided into four groups, according to the month of birth: born in spring (III–V), born in summer (VI–VIII), born in autumn (IX–XI), and born in winter (XII–II). Next, the subjects were divided into two groups: born in summer months (VI–VIII) and born in the other months (IX–V). Results In the first cohort, subjects born in the summer reach menarche significantly earlier than subjects born in other seasons. The same tendency was noticeable in subjects born in the years 1992–1994; however, the differences were not statistically significant. In both cohorts, girls born in summer months had their first menstruation at a younger age than girls born in other months. The difference in age at menarche between season/months was also seen after dividing the data into uniform groups in terms of SES. Conclusion The present data suggest that the season of birth influences sexual maturation rate in women. Am. J. Hum. Biol. 28:226–232, 2016. © 2015 Wiley Periodicals, Inc.